Public Private Partnership Dalam Penerapan Terminal Parkir Elektronik (Tpe) Di Pd Parkir Kota Makassar - Ayu, Yustika; Fatmawati, Fatmawati; Nasrulhaq, Nasrulhaq (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
This studi purposed to manage parking in Makassar City,through a public private partnership in the implementation of elektronik parking terminals (TPE) in the Makassar City Parking PD with the aim to increase regional original revenue (PAD). The research method used qualitative research with phenomenological research type.Data collection was carried out throught observation,interviews and documentation of informants directly involved .the result of this study showed that the public private partnership in the implementation of elektronik parking terminals (TPE) in PD Parking Makassar City was seen from the characteristics of the partnership (1) the was a written agreement in the determining partnership (2) objectives in the partnership (3) sharing of responsibilities for riks (4) resources,costs and benefits.then seen from the pattern of partnerhip interaction,Namely (1) the government regulates,controls and evaluates independently  (2) there was interaction between the government and the community.